Class-Wide Function-Related Intervention Teams "CW-FIT" Efficacy Trial Outcomes. (July 2015) - Kamps, Debra; Wills, Howard; Dawson-Bannister, Harriett; Heitzman-Powell, Linda; Kottwitz, Esther; Hansen, Blake; Fleming, Kandace
The purpose of the study was to determine the efficacy of the Class-Wide Function-Related Intervention Teams (CW-FIT) program for improving students' on-task behavior, and increasing teacher recognition of appropriate behavior. The intervention is a group contingency classroom management program consisting of teaching and reinforcing appropriate behaviors (i.e., getting the teacher's attention, following directions, and ignoring inappropriate behaviors of peers). Seventeen elementary schools, the majority in urban and culturally diverse communities, participated in a randomized trial with 86 teachers (classrooms) assigned to CW-FIT, and 73 teachers (classrooms) assigned to the comparison group. Class-wide student on-task behavior improved over baseline levels in the intervention classes. Teachers were able to implement the intervention with high fidelity overall, as observed in adherence to 96% of the fidelity criteria on average. Teacher praise and attention to appropriate behaviors increased, and reprimands decreased. These effects were replicated in new classrooms each of the 4 years of the study, and for all years combined.